Genome-wide analysis yields new loci associating with aortic valve stenosis - Anna Helgadottir (Nature Portfolio, 2018)
Aortic valve stenosis (AS) is the most common valvular heart disease. Here the authors identify two new AS loci that also associate with bicuspid aortic valve, aortic root diameter and/or coronary artery disease implicating both developmental abnormalities and atherosclerosis-like processes in AS.